A larger sense of purpose : higher education and society - Shapiro, Harold T., 1935- (Princeton University Press, 2005)
Universities were once largely insular institutions whose purview extended no further than the campus gates. Not anymore. Today's universities have evolved into multifaceted organizations with complex connections to government, business, and the community. This thought-provoking book by Harold Shapiro, former president of both Princeton University and the University of Michigan, and Chairman of the National Bioethics Advisory Commission under President Bill Clinton, explores the role the modern university should play as an ethical force and societal steward.